Biomarkers of inflammation and left ventricular remodelling in psoriasis patients treated with infliximab. (24th June 2022) - Midtbø, Helga; Kringeland, Ester; Gerdts, Eva; Ueland, Per Magne; Meyer, Klaus; Linde, Anja; Ulvik, Arve; Jonsson, Roland; Tveit, Kåre Steinar
Objective: Psoriasis is an immune mediated disorder associated with T cell activation and cardiovascular disease (CVD). We explored the association of inflammation with left ventricular (LV) remodelling in psoriasis patients receiving treatment with the tumour necrosis factor-α (TNF-α) blocker infliximab.Methods: Psoriasis patients ( n = 47, age 47 ± 14 years, 66% men) and 99 control subjects without psoriasis (age 47 ± 11 years, 72% men) were examined by echocardiography in a cross-sectional study. LV remodelling was assessed by LV mass index for height in the allometric power of 2.7. Serum concentrations of C-reactive protein (CRP), serum amyloid A (SAA), neopterin, kynurenine:tryptophan ratio (KTR) and the pyridoxic acid ratio (PAr) index were measured.Results: Serum concentration of neopterin ( p = .007) was higher in psoriasis patients, while the other inflammatory biomarkers had similar levels. LV mass index was lower in patients than controls (35.6 ± 9.6 g/m 2.7 vs. 40.3 ± 9.8 g/m 2.7, p = .008). In the total study population, serum SAA (β = 0.18, p = .02), KTR (β = 0.20, p = .02) and the PAr index (β = 0.26, p = .002) were all associated with higher LV mass index independent of age, sex, body mass index, hypertension, smoking, renal function and psoriasis. Also in psoriasis patients, higher SAA level (β = 0.34, p = .02), KTR (β = 0.32, p = .02) and the PAr index (β = 0.29, p = .05) were associated with higher LV mass index independent of body mass index, hypertension and diabetes.Conclusion: Higher levels of the inflammatory biomarkers SAA, KTR and the PAr index were associated with greater LV mass index in psoriasis patients, indicating a role of chronic inflammation in LV remodelling evident even during treatment with TNF-α blockers.